2023
DOI: 10.1371/journal.pone.0272897
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and predictive factors of antenatal care in Burundi: A spatial and multilevel baseline analysis for the third burundian demographic and health survey

Abstract: Introduction The use of antenatal care by pregnant women enables them to receive good pregnancy monitoring. This monitoring includes counseling, health instructions, examinations and tests to avoid pregnancy-related complications or death during childbirth. To avoid these complications, the World Health Organization (WHO) recommends at least four antenatal visits. Therefore, this study was conducted to identify predictive factors of antenatal care (ANC) among women aged 15 to 49 years and its spatial distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…However, Christian women are more likely to partake in these programs while Muslim women place more value on the knowledge transmitted to them by their mothers and women in their families. This result agrees with that of other studies in which Christian women were more likely to use the services of skilled midwives in Guinea [56]; this is also a proven fact in the case of Muslims in sub-Saharan Africa [57], India [58], Bangladesh [59], Ethiopia [60], and Nigeria [61], but not those in Burundi [62].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, Christian women are more likely to partake in these programs while Muslim women place more value on the knowledge transmitted to them by their mothers and women in their families. This result agrees with that of other studies in which Christian women were more likely to use the services of skilled midwives in Guinea [56]; this is also a proven fact in the case of Muslims in sub-Saharan Africa [57], India [58], Bangladesh [59], Ethiopia [60], and Nigeria [61], but not those in Burundi [62].…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, Muslim women who attended prenatal classes before giving birth for the first time stated that these classes gave them practical tools to prepare for labor and delivery, and found them helpful in providing reassurance about giving birth, relieved their fears, prepared them psychologically, and made them feel more comfortable about what the experience might entail [62]. As mentioned before, those who did not attend prenatal classes found the information they needed in consultation with family [63].…”
Section: Discussionmentioning
confidence: 99%
“…Despite antenatal care (ANC), delivery and postnatal care being free at the point of use in Burundi, utilization of these services remains low: between 2011 and 2017, only 49% of pregnant women attended at least four ANC visits [20]. Some of the factors identified in this study suggested that factors such as women’s education, their husbands’ education level, where they live, whether they plan to become pregnant, family income, and the household wealth index are factors that influence whether they used antenatal care [19].…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of Antenatal visits in Burundi is majorly below 6%, only the region of Bujumbura-Mairie has the highest ANC prevalence (24. 6%) and the lowest is in the West region (2.7%) [19]. Despite antenatal care (ANC), delivery and postnatal care being free at the point of use in Burundi, utilization of these services remains low: between 2011 and 2017, only 49% of pregnant women attended at least four ANC visits [20].…”
Section: Resultsmentioning
confidence: 99%